Timing of Maximal Weight Reduction Following Bariatric Surgery: A Study in Chinese Patients - Xu, Ting; Wang, Chen; Zhang, Hongwei; Han, Xiaodong; Liu, Weijie; Han, Junfeng; Yu, Haoyong; Chen, Jin; Zhang, Pin; Di, Jianzhong (Frontiers in Endocrinology, 2020)
Introduction: Bariatric surgery is a well-received treatment for obesity with maximal weight loss at 12–36 months postoperatively. We investigated the effect of early bariatric surgery on weight reduction of Chinese patients in accordance with their preoperation characteristics. Materials and Methods: Altogether, 409 patients with obesity from a prospective cohort in a single bariatric center were enrolled retrospectively and evaluated for up to 4 years. Measurements obtained included surgery type, duration of diabetic condition, besides the usual body mass index data tuple. Weight reduction was expressed as percent total weight loss (%TWL) and percent excess weight loss (%EWL). Results: RYGB or SG were performed laparoscopically without mortality or complications. BMI generally plateaued at 12 months, having decreased at a mean of 8.78 kg/m2. Successful weight loss of >25% TWL was achieved by 35.16, 49.03, 39.22, 27.74, 20.83% of patients at 6, 12, 24, 36, and 48 months after surgery. Overall, 52.91% of our patients had lost 100% of their excess weight at 12 months, although there was a rather wide range among individuals. Similar variability was revealed in women of child-bearing age. Conclusion: Chinese patients undergoing bariatric surgery tend to achieve maximal weight loss and stabilization between 12 and 24 months postoperatively, instead of at >2 years. The finding of the shorter stabilization interval has importance to earlier intervention of weight loss related conditions and women's conception planning.